Manajemen Transportasi : Kerugian Transportasi Akibat Kemacetan Lalu Lintas di Aceh - MG. Brilliant; Roy Raja Sukmanta Meilala; Delfia Herwanis (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
Due to population growth and the increasing number of vehicles, traffic congestion has become a major problem in Aceh, especially in large cities like Banda Aceh and Aceh Besar. This chaos has led to increased fuel costs, decreased productivity, and wasted time. Environmental factors such as increased carbon emissions and noise also affect the community's quality of life. The aim of this research is to study how traffic congestion impacts the fields of transportation, economy, and environment in Aceh. This study will also seek the main causes of congestion, such as the lack of public transportation, the imbalance between the number of vehicles and road capacity, and the non-ideal urban spatial patterns. We conducted the research using a descriptive qualitative approach, which involved direct observation, semi-structured interviews, and document analysis. The research results show that improving road infrastructure, better urban planning, and higher quality public transportation are strategic steps to reduce congestion. The sustainable solution suggested by this study is the integration of technology in community awareness campaigns and traffic management. We expect these findings to assist Aceh policymakers in addressing congestion, enhancing mobility, and fostering economic growth.